Isolation and expression analysis of Cu/Zn superoxide dismutase genes in sugarcane and the wild species Saccharum arundinaceus. Issue 1 (2nd January 2018) - Yao, Yanli; Liu, Yang; Hu, Xiaowen; Xing, Shulian; Xu, Lei
ABSTRACT: Saccharum arundinaceus is one of the most important species of sugarcane related species, and with strong resistance. Superoxide dismutases (SODs) play an important role in stress tolerance in plants. In this paper, two novel full-length cDNA sequence of the Cu/Zn SOD gene, denoted as SaSOD-1a and SoSOD1a (GenBank Accession number KJ002569 and KT327179), were isolated from S. arundinaceus and sugarcane, respectively. SaSOD-1a cDNA is 689 bp in length, including 33 bp of 5'-untranslated region (UTR) and 35 bp of the 3'-UTR, and a 621-bp open reading frame (ORF) encoding a 206 amino-acid sequence of the protein which has a conserved domain of superoxide dismutase belonging the SOD family. The SoSOD1a sequence is 690 bp, containing a 600 bp ORF, a 36-bp 5'-UTR and 54-bp 3'-UTR. It encoded the 199 amino-acid sequence of the protein which also has a conserved domain of superoxide dismutase belonging the SOD family. Between these two sequences, there was 97.5% similarity, 17 single nucleotide polymorphism (SNP) sites and 4 small insertion/deletion fragments; 95.5% protein similarity and 10 amino-acid mutation sites. In homologous evolutionary analysis, the Cu/Zn SOD genes from different plant species were rather conservative. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) analysis showed that the prokaryotic expression product was a fusion protein. Real-time quantitative polymerase chain reaction analysis demonstrated that the expression profile of SaSOD-1a and SoSOD1a were different under various drought stress duration. It was also suggested that SOD1a has a different drought response mode in sugarcane and the wild species S. arundinaceus.